An unexpected carboxylato-bridged-only hexanuclear copper compound - Castro, Maria Ana (2011)
The reaction of copper acetate with 3,4,5-tri(ethoxy)benzoic acid leads to the formation of dodecakis((μ-(3,4,5-tri(ethoxy))benzoato- κ2O:O′)-hexa(copper(II)), [Cu6(O 2C≡C6H2(OCH2CH 3)3)12]. The new compound crystallizes in the triclinic system, space group P1̄ with Z = 2, solvated by disordered cyclohexane molecules. The Cu(II) ions are placed in O5 pentacoordinated environments provided by four carboxylate oxygen atoms in a pseudo square planar arrangement and a fifth oxygen atom that belongs to a more distant carboxylate group in the axial position. The Cu(II) centers occupy the corners of a trigonal antiprism. A carboxylato network links each copper center with other four, providing potential paths for exchange coupling between the Cu(II) centers. Variable temperature magnetic susceptibility measurements show a maximum at 8 K. An analysis based on the spin-Hamiltonian formalism and DFT-based broken symmetry computations provides insight into the magnetic exchange interactions between the metal centers.